"Betalicious Secret Cafe Company" / Fazianie Nasyimah Latip... [et al.] - Latip, Fazianie Nasyimah; Paulus, Jistasika; Galin, Junnly; Lai-if, Mellie Jane; Awg Ali, Siti Sabella (2012)
A business plan is a written description of our business's future. This document describes what we plan to do and how we plan to do it. Business plans can help perform a number of tasks for those who write and read them. They're used by investment-seeking entrepreneurs to convey their vision to potential investors. They may also be used by firms that are trying to attract key employees, prospect for new business, deal with suppliers or simply to understand how to manage their companies better. In our business plan, we will include our business goals, the strategies used to meet them, potential problems that may confront your business and ways to solve them, the organizational structure of our business (including titles and responsibilities), and finally, the amount of capital required to finance our venture and keep it going until it breaks even. • The first is the business concept, where we discuss the industry, our business structure, our particular product or service, and how we plan to make our business a success. • The second is the marketplace section, in which we describe and analyze potential customers: who and where they are, what makes them buy and so on. Here, we also describe the competition and how we'll position our self to beat it. • Finally, the financial section contains our income and cash flow statement, balance sheet and other financial ratios, such as break-even analyses.